Natężenie i struktura ruchu turystycznego w Leśnym Arboretum Warmii i Mazur im. Polskiego Towarzystwa Leśnego w Kudypach - Auguścik, Adriana (Leśne Prace Badawcze, 2020)
One possible way to improve the health and well-being of people, especially those living in large urban agglomerations, is to provide the opportunity to spend time in the forest, which helps rest and regeneration by enabling contact with nature. Forest areas managed by the State Forests are therefore publically available to tourists for recreational and educational purposes. A good example illustrating the scope of access to the forest and its resources, and at the same time indicative of the degree of interest in forest tourism, is the Polish Forest Society’s Forest Arboretum of Warmia and Mazury, run by the Kudypy Forest District in the Regional Directorate State Forests in Olsztyn. The purpose of this work was to study the attendance of people visiting the Arboretum in 2014-2018 taking the variability of interest in visiting the Arboretum depending on the season of the year and the age of tourists (adults vs. children) into account. In overall, children were observed to visit the Arboretum more often than adults, while the largest number of organized groups visited the Arboretum in 2014. The most popular month among both, children and adults, was May. Using a Student’s t-test, Pearson’s Chi-squared test and Cramer’s coefficient a significant relationship between adults and children visiting the Arboretum and the seasons was identified. Significant differences between the average number of visitors to the Arboretum among children and adults at a specific time of year was also observed.